Polimorfismos en genes de baja penetrancia como marcadores genéticos de riesgo de cáncer de mama familiar entre mujeres colombianas (2014)
Breast cancer is the most common female neoplasia worldwide. It´s estimated that most cases are sporadic, though between 10 to 15% of them have a positive family history of the disease. This familial predisposition has been associated with alterations i